Penerapan Website Berbasis Framework pada Sekolah Tinggi Ilmu Komunikasi Profesi Indonesia menggunakan Teknik Pengembangan yang Aman dan Efisien - Damayanti, Devi; Pratama, Firman (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
This Pengabdian Kepada Masyarakat aims to enhance the efficiency and security of the information system at Sekolah Tinggi Ilmu Komunikasi Profesi Indonesia through the implementation of a modern framework-based website. In the digital era, the need for responsive, secure, and efficient systems has become crucial to supporting academic and administrative processes. Through this activity, a website was developed using the framework, known for its strengths in efficiency and security. The implementation methodology involved several stages, including user needs analysis, system design, framework implementation, functional testing, and training for institutional staff. This approach was designed to ensure that the system developed not only meets user requirements but also safeguards institutional data from cybersecurity threats.The outcome of this activity is a website with key features such as academic data management, institutional information dissemination, and communication among stakeholders. The impact of this activity is the enhancement of the institution's technological capabilities in managing information digitally, contributing to the development of educational quality and public services. With this framework-based website, Sekolah Tinggi Ilmu Komunikasi Profesi Indonesia can become a more competitive and adaptive institution in response to advancements in information technology. Keywords: Pengabdian Kepada Masyarakat, website, framework, security, efficiency.